Fulfillment of The Rights of Wife and Children Post Divorce - Andrea, Fahmi Tiara Rahma; Awaliyah, Zakiah Nurul (MILRev: Metro Islamic Law Review, 2022)
If the marriage is broken up due to divorce, the former husband and wife concerned who are the father and mother of their children are still obliged to look after and educate their children. In the Compilation of Islamic Law, when a marriage is broken up by divorce, the ex-husband is given the obligation to give mut'ah to his ex-wife and children who have not yet been mumayiz, who are entitled to hadnanah. Rights at the time of divorce are efforts to empower the dignity of a woman. Thus, this paper aims to find out how when an ex-husband is negligent in fulfilling obligations towards his ex-wife and child. This is because when a divorce occurs because of divorce, a husband thinks that there is no more maintenance that must be given to his ex-wife so there are obligations that the ex-husband ignores.